MASALAH KEPECAHAN KAYU DALAM PENEBANGAN DI HUTAN JATI - Wesman Endom; Maman Mansyur (Jurnal Penelitian Hasil Hutan, 1991)
This preliminary research. was conducted with the aim of gathering uarious felling aspects in teak forests  (Tectona grandia  LF), which will be  used  for desining a practical, simple, and cheap equipment  to reduce log split  during felilng operation.it is found  in  the field  that the deviation of  falling direction in conventional method wa  larger than that  in mechanical method. An  average stump  height Was  still high and therefore, needs  improvement. This will increase the volume   of wood and income of the feller.  Therefore, appropriate control and  counselling of fellers are required.The  secondary data showed  that log splits may occur at  the bottom,  midle and top of tree felled. In Songgom (53 tree  samples), the  split occured :  18.9% at the bottom,  67.9%  at the midle and 13.2% at the top. In  cipeundeuy  (50  trees  samples), the  figures  were 6% at the   bottom,  46% at the  midle and 48% at the top.